Enhanced Li‐O2 Battery Performance in a Binary "Liquid Teflon" and Dual Redox Mediators. Issue 4 (6th March 2019) - Balaish, Moran; Gao, Xiangwen; Bruce, Peter G.; Ein‐Eli, Yair
Abstract: Low capacity, poor rechargeability, and premature cell death are major setbacks in the operation of Li‐O2 battery, hindering its practical application. A promising approach of meeting those challenges is via the use of redox mediators (RMs), promoting Li2 O2 solution phase formation upon cell discharge and an efficient oxidation on charging. The use of dual RMs decouples the electrochemical reactions at the cathode with formation/decomposition of Li2 O2, resulting in improved discharge capacity, lower charge overpotential, and cycle stability. Although Li‐O2 cell performance is no longer mitigated by an insulating Li2 O2, a major inherent barrier to implement viable and functioning Li‐air batteries lies in both limited O2 mass transport and pores clogging. Here, a record discharge capacity of 6 mAh cm −2 (60% increase), by combining dual RMs with "liquid Teflon" type perfluorocarbons binary system, is demonstrated. The combination of the two materials in the cell contributes to the enhanced cell performance manifested also in lower charge overpotential values throughout dozens of cycles. This is also attributed to the unique compact and an exceptionally smooth morphology of the Li2 O2 deposit layers at both ends of the air cathode. Abstract : This communication reports on resolving the challenge of Li‐air carbon‐based cathodes, associated with a flooding of the air channels, which prevents an effective utilization of the electrode. The generic introduction of a binary perfluorocarbons dual RedOx mediator system in Li‐air cells alters the Li2 O2 morphology, leading to a lower discharge/charge overpotential, manifested also with enhanced battery cycle life.